Xiphias gladius Linnaeus 1758 ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Xiphias gladius Linnaeus, 1758. Swordfish. To 457 cm (15 ft) TL (Eschmeyer and Herald 1983). Circumglobal; western Pacific Ocean north to southern Kuril Islands (Savinykh 1998); northern Vancouver Island (49°53.12’N, 128°09.50’W), British Columbia (Luke Halpin, pers. comm. to M.L.) to Valdivia, Chile (Chirichigno and Vélez 1998), including Gulf of California (Robertson and Allen 2015), and Islas Galápagos (Grove and Lavenberg 1997). Oceanic; depth: surface to 2,878 m (9,442 ft) (Collette et al. 2011). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 213, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...